2013
DOI: 10.4314/sokjvs.v11i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Babesia canis</i> and <i>Hepatozoon canis</i> in Zaria, Nigeria

Abstract: The study was carried out to show the prevalence of Babesia canis and Hepatozoon canis in dogs within Zaria. Between the months of May and August 2010, blood samples collected from 150 dogs were processed using Giemsa stained thin blood smear and examined for the presence of B. canis and H. canis. Of the 150 dogs sampled, 84 (56%) were males and 66 (44%) were females. 106 (70.7%) were adults aged 1 year and above while 44 (29.3%) were dogs below the age of 1 year. Local breeds numbered 111 dogs constituting (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 2 publications
4
12
5
Order By: Relevance
“…This is the first prevalence study of haemo-and GI parasites in hunting dogs in Zaria and its environs to the best of our knowledge. This result agrees with the findings of Okubanjo et al (2013), who reported a 17.3% prevalence of Babesia canis and Hepatozoon canis in dogs within Zaria. However, the prevalence was lower than that of 42.1%, previously reported by Kamani et al (2011) in North Central Nigeria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is the first prevalence study of haemo-and GI parasites in hunting dogs in Zaria and its environs to the best of our knowledge. This result agrees with the findings of Okubanjo et al (2013), who reported a 17.3% prevalence of Babesia canis and Hepatozoon canis in dogs within Zaria. However, the prevalence was lower than that of 42.1%, previously reported by Kamani et al (2011) in North Central Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…However, the prevalence was lower than that of 42.1%, previously reported by Kamani et al (2011) in North Central Nigeria. Differences in climatic conditions as well as proper veterinary services, especially presence of Veterinary Teaching Hospital in Zaria may contribute to the lower prevalence in Zaria (Okubanjo et al, 2013). The result of the current investigation showed 16.39% prevalence of Babesia canis, higher than 8.9% prevalence reported by Jegede et al (2014), and 11.66% by Obeta et al (2009) in Abuja during the months of October to December, and 10.2% reported by Amuta et al (2010) in Makurdi.…”
Section: Discussionmentioning
confidence: 99%
“…This is lower than the prevalence of 38.5% reported by Okubanjo et al, (2013) in Sokoto using microscopy also and this might be due to different geographical locations where the studies were carried out and the type of dogs that were sampled. The prevalence in this study is also much lower than 54% reported by Adamu et al, (2014) in Jos, Nigeria.…”
Section: Discussioncontrasting
confidence: 64%
“…However, this is similar to the findings from other studies in Praia, Cape Verde, (Gotsch et al, 2009), Plateau, Rivers and Kwara States in Nigeria using PCR (Kamani et al, 2013). Most other studies of blood-borne pathogens in dogs and other animals in Nigeria have been based on microscopy (Akande et al, 2010; Okeke et al, 2013; Okubanjo et al, 2013). The prevalence of infection was higher when molecular diagnosis was used (76.7%) compared to tentative clinical diagnosis (33.6%) and light microscopy (14.7%), and molecular diagnosis allowed identification of the specific agent present.…”
Section: Discussionmentioning
confidence: 99%